ANALISIS PERAN BEA MATERAI DALAM ADMINISTRASI PERPAJAKAN - Khairunissa Alisya Hasibuan; Dini Vientiany; Siti Aulia Zannah (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study aims to analyze the role of stamp duty in tax administration in Indonesia by reviewing aspects of document legality, taxpayer compliance, and the effectiveness of its implementation within the modern taxation system. The method used is a qualitative approach with a descriptive research type through a literature study sourced from scientific journals, books, and relevant laws and regulations. The results show that stamp duty plays an important role as a legal instrument that provides evidentiary power to documents and supports orderly tax administration. In addition, the implementation of electronic stamp duty offers convenience, efficiency, and increased transparency in transaction monitoring. However, its implementation still faces several challenges, such as low public understanding, limited digital literacy, and differences in interpreting existing regulations. Therefore, continuous efforts are needed through increased public outreach, regulatory strengthening, and technological optimization to support the effective implementation of stamp duty in a more modern, transparent, and accountable tax administration system.